Structural basis for norovirus inhibition by human milk oligosaccharides - Weichert, Stefan; Koromyslova, Anna D.; Singh, Bishal; Hansman, Satoko; Schroten, Horst; Hansman, Grant S. (Journal of virology, 2016)
Histo-blood group antigens (HBGAs) are important binding factors for norovirus infections. We show that two human milk oligosaccharides, 2′-fucosyllactose (2′FL) and 3-fucosyllactose (3FL), could block norovirus from binding to surrogate HBGA samples. We found that 2′FL and 3FL bound at the equivalent HBGA pockets on the norovirus capsid using X-ray crystallography. Our data revealed that 2′FL and 3FL structurally mimic HBGAs. These results suggest that 2′FL and 3FL might act as naturally occurring decoys in humans.